PEDAGOGICAL CONDITIONS OF PROFESSIONAL TRAINING COMPETENT PROFESSIONAL TEACHER (Pedagogy of Higher and Secondary Education, 2008)
In the article an author describe the problem of propation competent teacher of the vocational training for the professional educational system.